Pengujian Perangkat Lunak Sistem Informasi Peminjaman PlayStation dengan Teknik Boundary Value Analysis Menggunakan Metode Black Box Testing - Dekif Ahrizal; Maula Khaerul Miftah; Romi Kurniawan; Teguh Zaelani; Yulianti Yulianti (Jurnal Informatika Universitas Pamulang, 2020)
Testing on an application aims to check whether a program has run properly or there are still errors that must be corrected so that the program created will be a program that has good quality. In this study the software that will be reviewed using Black Box Testing is a PlayStation Loan Information Application System where this application aims to facilitate the admin (PlayStation rental) in data collection on the number of borrowers, as well as the return date of PlayStation borrowed by members, where there are 2 forms to be filled in. Member added data form, game added form during the loan. lending data information applications will be tested using Black Box Testing where this test only aims to see the program whether in accordance with the expected function or not without knowing the program code used. Black Box Testing Method consists of several techniques, including Equivalence Partitions, Boundary Value Analysis, Sample Testing, and so on. Among the many testing techniques, in this study the testing technique was chosen using Boundary Value Analysis. Boundary Value Analysis Techniques, are software testing techniques in which tests are designed to include representatives of boundary values in a range.